Molecular genetics of hypospadias and cryptorchidism recent developments. Issue 1 (26th October 2018) - Kalfa, Nicolas; Gaspari, Laura; Ollivier, Margot; Philibert, Pascal; Bergougnoux, Anne; Paris, Francoise; Sultan, Charles
Abstract : During the last decade, a tremendous amount of work has been devoted to the study of the molecular genetics of isolated hypospadias and cryptorchidism, two minor forms of disorders of sex development (DSD). Beyond the genes involved in gonadal determination and sex differentiation, including those underlying androgen biosynthesis and signaling, new genes have been identified through genome‐wide association study and familial clustering. Even if no single genetic defect can explain the whole spectrum of DSD, these recent studies reinforce the strong role of the genetic background in the occurrence of these defects. The timing of signaling disruption may explain the different phenotypes. Abstract :